2015
DOI: 10.3341/jkos.2015.56.7.1096
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Caffeinated Energy Drink Consumption on Intraocular Pressure in Young Adults

Abstract: Purpose: Several energy drinks containing a high content of caffeine are widely consumed among young adults. We examined the effects of caffeinated energy drinks on intraocular pressure (IOP) and blood pressure (BP) in healthy young subjects. Methods: In this prospective randomized, case-controlled cross over study conducted, from August to September of 2014, 40 healthy young volunteers (80 eyes) in their 20's and 30's drank 2 types of beverage each consumed after a 3-month washout period. The study participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
1
0
2
Order By: Relevance
“…změny v průběhu dne [20], změny pozice těla či hlavy [21][22][23], pohybová aktivita [24][25][26] nebo hypoxie [27,28]. Mezi další procesy, které mohou NOT významně ovlivnit, patří také pití vody [29][30][31] nebo konzumace kávy či energetických nápojů [32][33][34]. Většina studií udává nárůst NOT po konzumaci vody [31][32][33][34][35], přičemž glaukomoví pacienti se jeví jako více citliví oproti normální populaci [36][37][38].…”
Section: úVodunclassified
See 1 more Smart Citation
“…změny v průběhu dne [20], změny pozice těla či hlavy [21][22][23], pohybová aktivita [24][25][26] nebo hypoxie [27,28]. Mezi další procesy, které mohou NOT významně ovlivnit, patří také pití vody [29][30][31] nebo konzumace kávy či energetických nápojů [32][33][34]. Většina studií udává nárůst NOT po konzumaci vody [31][32][33][34][35], přičemž glaukomoví pacienti se jeví jako více citliví oproti normální populaci [36][37][38].…”
Section: úVodunclassified
“…Mezi další procesy, které mohou NOT významně ovlivnit, patří také pití vody [29][30][31] nebo konzumace kávy či energetických nápojů [32][33][34]. Většina studií udává nárůst NOT po konzumaci vody [31][32][33][34][35], přičemž glaukomoví pacienti se jeví jako více citliví oproti normální populaci [36][37][38]. V případě HRW však dopad na NOT nebyl dosud popsán.…”
Section: úVodunclassified
“…Caffeine is a widely consumed ingredient worldwide, and studies have reported equivocal effects on glaucoma [7][8][9][10][11]. Some research has indicated that caffeinated coffee consumption increases the risk of glaucoma associated with elevated IOP and plasma homocysteine level [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%